Determinants of the Decision of the People of Sibolga City to Use Islamic Bank Products - Amhar Maulana Harahap; Junda Harahap (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to see the effect of knowledge, promotion and motivation on the decision of the people of Sibolga city to use Islamic Bank products. This research is descriptive quantitative research by distributing questionnaires as a data collection method. The sample in this study were 95 respondents who were people of Islamic Banks in Sibolga City. The data analysis technique uses the application (statistical product and service solutions) SPSS version 23. The results of this study indicate that there is no effect of knowledge on the decision of the people of Sibolga city to use Islamic Bank products. There is a promotion on the decision of the people of Sibolga city to use Islamic Bank products. There is knowledge motivation on the decision of the people of Sibolga city to use Islamic Bank products. There is an influence of knowledge, promotion and motivation on the decision of the people of Sibolga city to use Islamic Bank products.